The impact of the COVID-19 pandemic on the operation of shopping centres and stakeholders’ interests - Knecht-Tarczewska, Maria (Wpływ pandemii COVID-19 na funkcjonowanie centrów handlowych oraz na sytuację ich interesariuszy, 2021)
Shopping centres are an inseparable element of modern cities, influencing their socioeconomic space. The article presents the impact of the COVID-19 pandemic on the operation of shopping centres and interests of stakeholder groups. Theoretical considerations were undertaken based on the literature overview and results of chosen market reports. The synthesis and systematization of previous research characterising the ways in which stakeholders of shopping centers have been affected by the pandemic, provide the article’s contribution to the existing knowledge on the impact of COVID-19 on retail. The analysis provides critical insights and indicates problem areas that require special attention from researchers and business practitioners. The article constitutes a voice in the scientific discussion on retail development with a particular focus on shopping centers.
Biblioteka Regionalisty, 2021, Nr 21, s. 28-40
Keywords: retail; shopping centers; stakeholders; COVID-19; handel; centra handlowe; interesariusze